HUBUNGAN RESPONSE TIME DENGAN KECEMASAN KELUARGA PASIEN DI INSTALASI GAWAT DARURAT (IGD) RSI PKU MUHAMMADIYAH TEGAL - Irawan, Deni; Ni’mah, Jumrotun; Kurniawan, Eka Nanda (Juru Rawat. Jurnal Update Keperawatan, 2025)
Anxiety among patients’ families often occurred while waiting for medical treatment in the Emergency Department (ED). Several studies in Indonesia reported that more than 50% of patients’ families experienced moderate to severe levels of anxiety. One of the contributing factors was the response time of medical personnel in providing care. This study aimed to analyze the relationship between response time and the anxiety levels of patients’ families at the Emergency Department of RSI PKU Muhammadiyah Tegal. A quantitative approach with a descriptive correlational design and a cross-sectional method was applied. A total of 96 respondents were selected using accidental sampling. Data collection instruments included an observation sheet to measure response time and a questionnaire to assess anxiety levels. The results of the Chi-Square test showed a significant relationship between response time and family anxiety (p-value = 0.000; X² = 96.000). These findings indicated that the faster the patient received treatment, the lower the level of anxiety experienced by the family. This study was expected to serve as input for hospital management to improve the service system by accelerating the response time of medical personnel in order to reduce the anxiety experienced by patients’ families in the Emergency Department.